2021
DOI: 10.1063/5.0035343
|View full text |Cite
|
Sign up to set email alerts
|

n-type GaN surface etched green light-emitting diode to reduce non-radiative recombination centers

Abstract: In this study, we attempt to identify the presence of surface defects (SDs) at an n-type GaN surface after high-temperature growth and gain insight into their intrinsic features. To this end, first, we carefully investigate n-type GaN samples with different surface etching depths. Low-temperature photoluminescence (PL) spectra reveal that SDs are most likely nitrogen vacancies (VN) and/or VN-related point defects intensively distributed within ∼100 nm from the n-type GaN surface after a high-temperature growth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 40 publications
0
13
0
Order By: Relevance
“…Other macroscale studies have also detected two types of PDs in InGaN/GaN QWs. 17,19 Evidence suggests midgap (type-I) defects are intrinsic nitrogen vacancy complexes, 21,40 while the type-II defect may be linked to impurities such as oxygen or carbon. 41 All these results highlight the versatility of our CL analysis to extract this information directly from images of PDs, and have particular relevance for III-nitride devices based on InGaN.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Other macroscale studies have also detected two types of PDs in InGaN/GaN QWs. 17,19 Evidence suggests midgap (type-I) defects are intrinsic nitrogen vacancy complexes, 21,40 while the type-II defect may be linked to impurities such as oxygen or carbon. 41 All these results highlight the versatility of our CL analysis to extract this information directly from images of PDs, and have particular relevance for III-nitride devices based on InGaN.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, their results also associate these defects with a near-midgap energy level and identify another energy level near the valence band edge which could match our type-II defects. Other macroscale studies have also detected two types of PDs in InGaN/GaN QWs. , Evidence suggests midgap (type-I) defects are intrinsic nitrogen-vacancy complexes, ,, whereas the type-II defect may be linked to impurities such as oxygen or carbon …”
mentioning
confidence: 96%
See 1 more Smart Citation
“…92 In particular, dislocations and point defects serve as nonradiative recombination centres that introduce the defect levels into the bandgap of III-nitrides and reduce the possibility of radiative recombination by capturing carriers, finally degrading the IQE of LEDs. [93][94][95][96] Moreover, fundamental bottlenecks including efficiency droop 97 and green gap 98 encountered by III-nitride LEDs are found to be closely related with dislocation density, which adversely affects IQE and thus degrades optoelectronic properties of LED devices.…”
Section: Dislocation Density Reduction By Pssmentioning
confidence: 99%
“…Several physical mechanisms have been suggested as the origin of the green gap, including the quantum-confined Stark effect, random alloy fluctuation, high dislocation density, and asymmetric carrier distribution. Besides these, the high level of defect incorporation in the multiple-quantum-well (MQW) active layer has often been discussed as a potential contributor to the green gap. Recent studies have revealed that the defect incorporation originated from two independent mechanisms: (i) inherent incorporation of impurities, such as carbon and oxygen, due to reduction in the growth temperature to grow the indium (In)-rich MQWs , and (ii) incorporation of the native defects formed at an n-type GaN surface [i.e., surface defects (SDs)] into the MQWs during the LT growth. Both mechanisms create nonradiative recombination centers (NRCs) in the MQW active layer, which act as a path for Shockley–Read–Hall (SRH) nonradiative recombination, thereby reducing IQE. , Recently, studies on the second of the above-mentioned mechanism are being actively conducted by several research groups as it is considered a key factor in the IQE improvement. Our recent studies showed that the SDs in an n-type GaN are most likely nitrogen vacancies (V N ), divacancies comprising Ga and N vacancies (V Ga V N ), and/or a V N impurity complex, which are intensively distributed within about 100 nm from the growth surface of n-type GaN. , Note that the SDs are easily incorporated with In atoms owing to strong affinity between them; therefore, an introduction of a GaInN or AlInN layer between the n-type GaN and the MQWs [i.e., an underlying layer (UL)] is very useful to improve the IQE by trapping the SDs therein. , However, a further increase in the In content and/or thickness of the UL to enhance the SD trapping frequently has negative impacts on the device performance because it generates threading dislocations (TDs) and absorbs the photons emitted from the MQWs. , This indicates that the introduction of a UL alone is insufficient to suppress the incorporation of SDs into the MQWs. As a method to further reduce the SDs in n-type GaN other than the introduction of a UL, we have demonstrated the MQWs grown on the surface-etched n-type GaN layer, which showed an improvement in the IQE by a factor of 2.5 in green LEDs .…”
Section: Introductionmentioning
confidence: 99%